Pengembangan Konten Nilai-Nilai Kecerdasan Emosional dalam Materi Pembelajaran Fisika pada Bahan Ajar - Kamus, Zulhendri; Asrizal, Asrizal; Putri, Aufha Diny (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Learning of physics according to the curriculum 2013 emphasizes the comprehensive achievement of student competence, so that the equality between soft skills and hard skills is formed. The role of learning materials especially physics subject is very important to support implementation of curriculum for physics learning. In fact, the knowledge and skills content of physics learning materials used students in school is more than attitude content. Development of physics learning materials integrated the values of emotional intelligence is the alternative solution of this problem. This research use Research and Development (R&D) method. This paper explains results of preliminary and main field testing of the physics learning materials integrated the values of emotional intelligence. This product has a validity value of around 85.83 or a very valid category. Based on data analysis, there are two results from this research. First, the practicality value of product according to teacher and student are an average score of 88.1 and 82 respectively or very high category.  Second, the physics learning materials integrated emotional intelligence values is effective to improve the student competences in learning. The results of research indicate that the emotional intelligence value developed in physics material is feasible using in physics learning than it able to realize the comprehensive competence achievement.